Behavioral city - Viale, Riccardo (Frontiers in Built Environment, 2025)
Behavioral City is a new concept that aims to integrate the behavioural approach of city policy making and the behavioural approach of urban planning. Behavioral Urbanism (BU) and its related area of study, behavioural architecture, is an interdisciplinary field focused on the interaction between humans and the built environment, studying the effects of social, cognitive and emotional factors in understanding the spatial behaviour of individuals. Behavioral Public Policy (BPP) is an approach to public policy that uses the tools of cognitive science and behavioural economics to identify how to change citizen behaviour towards individual and collective wellbeing goals.